Myvatn 1951 - Scott, Peter (Wildfowl, 1952)
Both before and after the main expedition to the Pinkfoot breeding grounds in the Central Highlands, short visits were paid to Myvatn, a shallow lake in north-eastern Iceland, which probably holds the greatest breeding concentration of Western European ducks.